Myoepithelial cells in pathology - N Balachander; K. M. K. Masthan; N Aravindha babu; V Anbazhagan (Wolters Kluwer Medknow Publications, 2015)
Myoepithelial cells are a normal constituent of the salivary acini and ducts and are found between the epithelial cells and the basement membrane. Microscopically myoepithelial cells are thin and spindle-shaped and ultrastructurally they possess a number of Cytoplasmic processes that extend between and over the acinar and ductal-lining cells, and they show features of both smooth muscle and epithelium. They play a vital role during expulsion of saliva and regulates the electrolytic exchange. They also perform as tumor suppressors and are considered to play a very important role in differentiation of various salivary gland tumors and help in the diagnosis of tumors. Neoplastic myoepithelial cells in both benign and malignant tumors can take numerous forms including epithelioid, plasmacytoid, spindle and clear cell variant, and this variability largely accounts for difficulties in histopathological diagnosis.